Makna Gelar Yesus sebagai Mesias dan Implementasinya bagi Kehidupan Umat Kristen dalam Masyarakat Majemuk di Indonesia - Ronaldo Stefanus (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
This research investigates the meaning contained in the title “Jesus as Messiah” and how this concept is implemented in the daily lives of Christians in Indonesia, a pluralistic society with diverse cultures and religions. Using a theological and social approach, this research eplores Christians’ understanding of the identity of the Messiah and its impact on religious practices and their interactions in a multicultural environment.